Fabrication and Microstructure of Self-Supporting Thin Ceramic Electrolytes Prepared by Laser Machining. (2nd June 2015) - Cebollero, Jose Antonio; Lahoz, Ruth; Laguna-Bercero, Miguel Angel; Peña, Jose Ignacio; Larrea, Angel; Orera, Victor M
Abstract : Self-supporting thin Yttria Stabilized Zirconia (YSZ) ceramics electrolytes have been prepared by laser machining. They are carved from a sintered YSZ plate to shape a 20 µm thick and 8 mm in diameter central region, surrounded by an unprocessed 150 µm thick supporting zone. Scanning Electron Microscopy (SEM) and Electron BackScattering Diffraction (EBSD) studies confirmed that the strains produced by the laser processing are small and limited to only one or two layers of YSZ grains (~5 µm). SEM and Transmission Electron Microscopy (TEM) have been also used to characterize the surface of the membrane. It is corrugated and coated with YSZ nanoparticles as a result of the laser plasma deposition. Electrochemical characterization by Impedance Spectroscopy (EIS) showed that this surface morphology improves the electrical performance of the membrane slightly but clearly, reducing the cathode polarization resistance by about 5% in the 650-850 ºC range.